A comparative study of MTA solubility in various media - Saghiri, Mohammad Ali; Ricci, Jack; Daliri Joupari, Morteza; Aeinehchi, Mohammad; Ahmadi, Kamran; Bahramian, Niloofar (Iranian Endodontic Journal, 2011)
INTRODUCTION: Solubility of root filling materials is heavily influenced by the environment they are in contact with. This study compared the solubility of ProRoot MTA in deionized water and synthetic tissue fluid. MATERIALS & METHODS: Forty specimens of prepared MTA were immersed in deionized water and synthetic tissue fluid (20 samples each). The solubility was assessed after 7 and 28 days. Scanning electron microscope observation was also performed. The mean weight loss was evaluated using a digital scale. Data were analyzed using one-way ANOVA. Tukey test was performed for multiple comparisons. RESULTS: MTA solubility in synthetic tissue fluid was significantly lower than deionized water after 7 and 28 days (P<0.05). Secondary electron detectors revealed the presence of lumps and platelets on the surfaces of both specimens. Also, more voids were observed in specimen stored in deionized water. CONCLUSION: MTA dissolved faster in deionized water than synthetic tissue fluid. Despite this, the solubility of this material in both media was acceptable.